Urban infrastructure in North Eastern States - Singh, Amit Kumar (2011)
The north eastern part of Indiaa is one of the least urbanised regions in the country, however sice last five decades the tempo of urbanization is very much higher in most of the states of the region. But as urban population continues to increase, more and more people will have to share whatever the facilities and services are available in the urban centres. There will be more demand for different basic amenities and services resulting in increased pressure on urban infrastructure. This article aims to analyse the availability of basic services and amenities in the urban centres of the North Eastern States of India. As per the data a large proportion of the urban population do not have access to these basic amenities. A comparison with the urban India, taken as a whole is also being made in this article. - Reproduced.
Keywords: Urbanization